Contributions to the taxonomy of some Amazonian Stygnidae (Opiliones: Laniatores: Gonyleptoidea) - Villarreal, Osvaldo; Kury, Adriano B.; Colmenares, Pío A. (Zootaxa, 2021)
Some taxonomic changes are made in Amazonian Stygnidae, based on reinterpretation of generic boundaries: (1) the hitherto monotypic genus Jime Pinto-da-Rocha & Tourinho, 2012 is newly recorded from Venezuela: Jime praecursor spec. nov. (Tobogán de la Selva, Amazonas state) is described and a new generic diagnosis is provided. The genital chaetotaxy is interpreted for the two known species of Jime, and (2) three species which have been originally described as Stygnoplus Simon, 1879 are herein newly transferred to Yapacana Pinto-da-Rocha, 1997 (hitherto monotypic): Y. ianomami (Pinto-da-Rocha & Tourinho, 2012) comb. nov., Y. neblina (Pinto-da-Rocha & Tourinho, 2012) comb. nov., and Y. tapirapeco (Pinto-da-Rocha & Tourinho, 2012) comb. nov. A key for identification of males of the genus Yapacana is offered.